Answer:
f(x) = 3x+2
g(x) = 2x - 2
To find (f-g)(x)
(f-g)(x) = f(x) - g(x)
Substitute f(x) to 3x+2 and g(x) to 2x -2
(f-g)(x) = (3x+2) - (2x-2)
Open the brackets
(f-g)(x) = 3x+2-2x+2
Rearrange
(f-g)(x) = 3x-2x+2+2
(f-g)(x) = x + 4
Answer is option A = x + 4
Step-by-step explanation:
5:7 (pencils to pens)
7/12 chance that a pen from the first box will be selected.
4:4 (colour pencils to crayons)
4/8 = 1/2 chance that a crayon from the second box will be selected.
The probability of picking both:
7/12 * 1/2 = 8/24 = 1/3
Answer:
f(1) = 24
Step-by-step explanation:
f(1) is the value of f(x) when x = 1, that is from the table
f(1) = 24
Answer:
c
Step-by-step explanation:
-7.5 is less than 6.5
Answer:
79%
Step-by-step explanation: